STRATEGI PEMBERDAYAAN GURU UNTUK MENGEMBANGKAN UNIT PRODUKSI BERBASIS SEKOLAH DI SLBN BALIKPAPAN - Waskitoningtyas, Rahayu Sri; Casmudi; Dewi; Febrianti, Ine (Jurnal Terapan Abdimas, 2026)
Abstract. The purpose of this Community Service Program is to determine the percentage of teachers'  understanding regarding strengthening school-based production units and what digital media accounts are created to increase marketing. The location of this community service program is at SLBN Balikpapan, which will be implemented in July 2025. The target is teachers at SLBN Balikpapan. The approach in this community service program uses Participatory Action Research (PAR). This Community Service activity has succeeded in empowering teachers in developing a bread production unit at SLBN Balikpapan in a structured manner. Teachers not only play a role as instructors, but also as drivers of school-based entrepreneurship. There is an increase in teachers in participating in the socialization of strengthening school-based production units by 81.69%; and the creation of Shopee and Shopee Food accounts.    Abstrak. Tujuan PkM ini untuk mengetahui seberapa persen pemahaman guru terkait penguatan unit produksi berbasis sekolah serta akun media digital apa yang dibuat untuk peningkatkan pemasaran. Tempat pelaksanaan pengabdian ini di SLBN Balikpapan yang dilaksanakan pada bulan Juli 2025. Dengan sasarannya para guru di SLBN Balikpapan. Pendekatan dalam pengabdian ini menggunakan Participatory Action Research (PAR). Kegiatan Pengabdian kepada Masyarakat ini berhasil memberdayakan guru dalam mengembangkan unit produksi roti di SLBN Balikpapan secara terstruktur. Guru tidak hanya berperan sebagai pengajar, tetapi juga sebagai penggerak kewirausahaan berbasis sekolah. Adanya peningkatan guru dalam mengikuti sosialisasi penguatan unit produksi berbasis sekolah sebesar 81,69%; dan pembuatan akun shopee dan shopee food.